Strategie nauczania w dysfunkcjach na lekcjach historii i WOS. Wybrane zagadnienia - Bugajska-Więcławska, Joanna (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2022)
The problem of difficulties encountered by pupils with dysfunctions during their history and social studies lessons is discussed in this article. The principal method of assessing the cognitive capabilities and competences of those children which was employed in this paper is the analysis of narrative and logical-abstract competences of those children, including the ability to order the studied material. The text is based on research and observations made by the author as well as materials on the problem prepared for the course „A pupil with special educational needs in history and social studies lessons” conducted by the author.
Keywords: strategie nauczania; dysfunkcje; kompetencje narracyjne; kompetencje logiczno-abstrakcyjne; historia; wiedza o społeczeństwie